1987
DOI: 10.1017/s0334270000005658
|View full text |Cite
|
Sign up to set email alerts
|

Properties of short-crested waves in water of finite depth

Abstract: Short-crested waves are defined as propagating surface gravity waves which are doublyperiodic in the horizontal plane. Linearly, the short-crested wave system we consider occurs when two progressive wavetrains of equal amplitude and frequency are propagating at an angle to each other.Solutions are calculated via a computer-generated perturbation expansion in wave steepness. Harmonic resonance affects the solutions but Pade approximants can be used to estimate wave properties such as maximum wave steepness, fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 16 publications
0
48
0
Order By: Relevance
“…Not only does this method enjoy the stability properties of the TFE method for DNO (as compared to the OE and FE implementations), but also, and in contrast to the situation for computing DNO, it has a greatly reduced operation count in comparison to the Roberts algorithm. In fact, we showed that the computational complexity is O (NN 1 N 2 log(N y )N y + N 2 N 1 N 2 N y ) to be compared with O(N 3 N 2 1 N 2 2 ) for Roberts [70] and Marchant & Roberts [47]. With this efficiency and high-order stability we are now able to produce extremely accurate simulations of highly nonlinear waveforms as we now demonstrate.…”
Section: For Demonstrations)mentioning
confidence: 67%
See 3 more Smart Citations
“…Not only does this method enjoy the stability properties of the TFE method for DNO (as compared to the OE and FE implementations), but also, and in contrast to the situation for computing DNO, it has a greatly reduced operation count in comparison to the Roberts algorithm. In fact, we showed that the computational complexity is O (NN 1 N 2 log(N y )N y + N 2 N 1 N 2 N y ) to be compared with O(N 3 N 2 1 N 2 2 ) for Roberts [70] and Marchant & Roberts [47]. With this efficiency and high-order stability we are now able to produce extremely accurate simulations of highly nonlinear waveforms as we now demonstrate.…”
Section: For Demonstrations)mentioning
confidence: 67%
“…(6)) provided c 0 satisfies (5) and, again, the linear operator (3) appears on the left-hand side of (27). As with the approach of Roberts et al [70,47], the velocity c n−1 is used to satisfy the solvability condition required by the singular nature of the system (27), while several parameterizations of the bifurcation curve can be given which produce a unique solution at every order; please see [61] for details. On the theoretical side, Reeder & Shinbrot [68] proved the existence of solution branches to (26) and parametric (i.e.…”
Section: For Demonstrations)mentioning
confidence: 93%
See 2 more Smart Citations
“…Analytical solutions have been provided by Chappelear (1961) and Hsu, Tsuchiya & Silvester (1979) to third order and by Ioualalen (1993) to fourth order. Roberts (1983), Roberts & Schwartz (1983) and Marchant & Roberts (1987) computed short-crested waves using a numerical perturbation method up to 27th and 35th order for deep water and finite depth, respectively. Roberts & Peregrine (1983) treated the important limit of grazing angles, where the short-crested deepwater waves become long-crested.…”
Section: Third-order Theory For Multi-directional Irregular Wavesmentioning
confidence: 99%